Metagenomic Analysis Of Microbiome In Bagworm, Metisa Plana Walker (Lepidoptera: Psychidae) - Andrew, Ting Chung Jie (2022)
The bagworm Metisa plana is one of the major pests in the oil palm plantation in Malaysia, with infestation that results in huge economical loss. However, the biology of the bagworm such as the microbiome has yet to be identified. Studying the microbiome of M. plana could provide insight on the problem as the bacteria associated with insects often provide numerous benefits to the insect itself. Using 16S rRNA sequencing, the study was conducted to compare the composition of the bacterial communities of two larval stages (early instar stage and late instar stage) from outbreak area, as well as comparing the late instar stage larvae from non-outbreak and outbreak areas. Generally, the bacterial community was dominated by Proteobacteria and Actinobacteria phyla while the Enterobacteriaceae was found to be the dominant family. The Proteobacteria phylum was found to be more abundant in the late instar stage (82.45%) than in the early instar stage (82.28%). At the family level, the Enterobacteriaceae was slightly more abundant in late instar stage (75.46%) than in early instar stage (75.29%). The instar stage was observed to have no significant impact on the bacterial variability and showed similar bacterial community structure. Proteobacteria was significantly more abundant in the outbreak area (82.02%) than in the non-outbreak area (20.57%). However, Actinobacteria was significantly more abundant in the non-outbreak area (76.29%) than in the outbreak area (14.16%). At the family level, Enterobacteriaceae was more abundant in outbreak area (75.41%) than in non-outbreak area (11.67%).